Re-description of Alburnus doriae, with comments on the taxonomic status of A. amirkabiri, A. mossulensis, A. sellal and Petroleuciscus esfahani (Teleostei: Cyprinidae) - Mohammadian-Kalat, Tooba; Esmaeili, Hamid Reza; Aliabadian, Mansour; Freyhof, Jörg (Zootaxa, 2017)
The taxonomic status of five nominal species of cyprinid fishes from the Middle East is reviewed by applying morphological and molecular (COI) characters. Alburnus populations from the Iranian Lake Namak basin, the Zayandeh River drainage and the upper Karun River drainage are identified as A. doriae. Petroleuciscus esfahani, from the Zayandeh River, as well as Alburnus amirkabiri, from the Lake Namak basin, are synonyms of A. doriae. Molecular data support treating Alburnus mossulensis and A. sellal as a single species. As First Revisers we give precedence to A. sellal over A. mossulensis.